EFFORTS TO IMPROVE DECISIONS IN ASSOCIATION OF CLASS VIII STUDENTS THROUGH COUNSELING GUIDANCE SERVICES USING THE PROJECT BASED LEARNING (PjBL) METHOD - Rubiati (CV. Asy Persada Quality, 2024)
This research aims to assess the effectiveness of implementing the Project-Based Learning (PjBL) method in improving the manners of class VIII students in the guidance and counseling subject. The research population includes all class VIII students for FY 2023/2024. The sample selection in this study used a random sampling method. The research was carried out in three cycles and at the end of each cycle a reflection was carried out on the actions given. Data collection techniques in research use observation sheets, questionnaires and documentation. The research instruments include an essay test to measure student politeness and a student activity questionnaire. The research results show that the implementation of counseling guidance services using the Project Based Learning method can improve students' politeness in socializing. This can be seen from the results of observing the percentage in cycle I, namely 70.3%, and cycle II which experienced an increase, namely 79.3%, after being provided with counseling guidance services using the project based learning method. This shows that the Project Based Learning learning model can improve students' manners in socializing through counseling guidance services.